Penatalaksanaan Fisioterapi pada Kasus Osteoatritis KNEE untuk Mengurangi Nyeri Gerak dengan Modalitas Infrared dan Latihan Closed Kinetik Chain - Annisa Annisa; Yulisha Eva Oktaviani; Muhammad Tahdi; Arfian Hamzah (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2024)
Osteoatritis is characterized by a decrease in joint synovial fluid, decreased muscle tone, joint cartilage becomes thinner, ligaments become stiffer, decreased elasticity and flexibility and a decrease in joint motion, one of the initial symptoms experienced is knee pain. This study aims to determine physiotherapy management in reducing motion pain in knee osteoatritis patients using Thermal Therapy Modalities, namely Infrared and Closed Kinetic Chain Exercises. This study uses a descriptive quantitative research type case study with 4 respondents conducted at Sultan Suriansyah Hospital Banjarmasin and at the home of each patient with Visual Analog Scale measuring instruments. After the therapy was carried out for 9 times, the pre-test results were obtained with the interpretation of no pain at 0%, mild pain at 40% and moderate pain at 60%. The post test results showed a decrease in pain, namely in the interpretation of no pain to 25% mild pain to 40% and moderate pain to 35%. Based on this data, it can be concluded that Infrared and CKC Exercise can reduce motion pain.